The adoption of digital transformation process by SMEs in Moroccan context: state of play - BELLANY , Kawtar; DHIBA , Youssef (Revue Internationale des Sciences de Gestion, 2024)
Today, interest in digital is unavoidable in companies at all levels, from small and medium-sized enterprises (SMEs) to large corporations and international groups. Companies now understand that they need to integrate digital into their overall strategy, in order to take full advantage of the opportunities offered by new digital technologies. This global trend is essential for adapting to a constantly economic environment, making digital transformation vital for any business entity. However, adopting digital transformation presents a variety of challenges, depending on the company's sector of activity and the needs dictated by changing markets. Through a systematic review of the literature, this article examines the key elements in the adoption of digital transformation by Moroccan SMEs, analyzes the state of their use of digital technologies and the prospects for their transformation in the Moroccan context. Finally, this article proposes an adoption model with three main components: " Field of adoption; Adoption; Effetcs and adoption Scenarios ".